Experiences of frontline nurses about the enayatak nursing model of care implemented in a public health care facility in the emirate of Abu Dhabi, United Arab Emirates - Hayton, Margaretha Elizabeth (Stellenbosch : Stellenbosch University, 2020)
Thesis (MNur)--Stellenbosch University, 2020.